Adaptation to Saline Intrusion in the Coastal Area of Vĩnh Châu, the Vietnamese Mekong Delta - Hagenvoort, J.E.J.; Trí, Văn Đăng Phạm (VNU Journal of Science: Earth and Environmental Sciences; Vol 29 No 3, 2013)
Abstract : The extraction of groundwater has increased rapidly over the past decades and forms one of the main causes of saline water intrusion into the coastal aquifers. Such the intrusion has been accelerated by the on-going rise of the sea level. Saline intrusion in groundwater in the Vietnamese Mekong Delta is highly complex as it depends heavily on different factors, including changes in water supplies (e.g. the magnitude of the annual upstream hydrograph during both the flood and dry seasons and timing distribution of the annual rainy season) and rising water demands (e.g. the amount of fresh groundwater extracted for different purposes like domestic, agriculture and aquaculture use). This article is to provide an insight into current adaptations to increasing salinity concentration in the groundwater resource in Vĩnh Châu - a coastal district of the Sóc Trăng province, the Vietnamese Mekong Delta. The existing adaptations to maintain the current livelihood of local residents were investigated and possible adaptations to sustain such the valuable fresh groundwater resources were proposed. In fact, adaptations have already taken place by switching from paddy rice to marine aquaculture over the last decades; however, it is not widely applicable due to high inputs and great economic risks. No problems were found in the current situation with farmers who grew upland crops on high sand ridges due to low salinity levels of the deep groundwater. However, decreases of yield in saline-sensitive agriculture irrigated by groundwater were experienced in the study area. Keywords: Saline intrusion, groundwater, climate change, adaptation, coastal area, and Vietnamese Mekong Delta.